In memoriam: David G. Robinson - Scheuring, David; Hillmer, Stefan; Schumacher, Karin (Protoplasma, 2025)
We are deeply saddened to report that David Gordon Robinson passed away on Tuesday, 5 November 2024. He has left behind his wife and three children. Without doubt, David was one of Europe’s leading plant cell biologists and electron microscopists, best known for his research on intracellular trafficking and cellular organization. He is leaving a legacy of groundbreaking research and influence in the field. In this obituary, we want to recapitulate the most important stages from the impressive career of a truly unique character.